Performance evaluation of a single mode optical fiber tip sensor for glucose detection - Nazirah Mohd Razali; Puteri Nadiah Syamimi Said Ja'afar; Sumiaty Ambran (Institute of Advanced Engineering and Science, 2020)
Glucose must be carefully regulated to ensure its safety and quality. Nowadays, chemists often face difficulty to measure glucose concentrations as the current methods for the analysis are expensive and require complex procedures which have reduced the interest among chemists to use these techniques. This study evaluated the performance of a single mode optical fiber tip sensor for glucose detection. The sensing mechanism mainly depends on the Fresnel’s reflection that occurs at the flat fiber tip region while the sensor performance was evaluated based on its sensitivity and linearity. The sensor was tested in glucose solution at different concentration range; high range (0% - 14%), medium range (0% - 1.4%) and low range (0% - 0.14%). The sensor showed a good performance when sensing the glucose solution at high and medium concentration range with strong linearity of more than 90% and an average sensitivity of 0.0979 dBm/% and 0.1019 dBm/%, respectively. However, the low concentration range showed no significant changes during sensing. Based on the findings obtained in this study, the optical fiber tip sensor has the potential to be utilized for glucose detection and suitable for high and medium concentration range measurement.